A factor limiting the accuracy of optical loss measurements in single-mode fibres: 'frozen-in' inhomogeneities of the Rayleigh backscatter coefficient. (February 2017) - Busurin, V.I.; Gorshkov, B.G.; Gorshkov, G.B.; Grinshtein, M.L.; Taranov, M.A.
Abstract: Backscatter coefficient fluctuations at a wavelength of 1560 nm in Fujikura FutureGuide-LWP, Corning ClearCurve XB and Corning SMF-28 ULL telecom fibres have been studied using optical time-domain reflectometry and broadband (10 nm) depolarised light. It has been shown that, under the conditions of our experiments, such fluctuations are 'frozen-in' and that a typical standard deviation in noiselike reflectograms is 0.16 dB, with a correlation distance no greater than 1 m. Such results have been obtained for all fibre samples. The effect studied experimentally limits the accuracy of attenuation measurements in optical fibres, especially at short fibre lengths (tens and hundreds of metres). Moreover, it should be taken into account in designing distributed physical parameter sensors using Rayleigh scattering intensity as a reference channel. Possible sources of the inhomogeneities in the fibres are discussed.